Bimetallic ZnFe2O4 nanosheets prepared via electrodeposition as binder-free high-performance supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Park, Chanwoo; Kim, Yongil; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
Binder-free bimetallic ZnFe2O4 nanosheets were fabricated using one-step electrodeposition, which facilitated excellent electrical contact between the ZnFe2O4 nanosheets and the nickel substrate. The resultant numerous ZnFe2O4 nanosheets with their cubic spinel structures promote interfacial activity to enhance the electrochemical and Faradaic redox reactions. The metallic Zn and Fe from the cubic spinel structure of ZnFe2O4 attract electrolytic ions and increase the energy-storage capability, thus yielding a specific capacitance of 1093 F.g(-1) at a current rate of 1 A.g(-1). Different samples were prepared by varying the amount of metal salts in the electrodeposition solution while maintaining a constant ZnNt:FeSO4 concentration ratio of 1:2 for all cases. The optimal electrode composition, which yielded an energy density of 54 Wh.kg(-1) and a capacitance retention of 93.5% at N = 5000 charge-discharge cycles, was identified.
Keywords: Bimetallic; Electrodeposition; Energy storage device; supercapacitor; ZnFe2O4 nanosheet

Cotton fabric decorated with manganese oxide nanorods as a supercapacitive flexible electrode for wearable electronics - Samuel, Edmund; Joshi, Bhavana; Kim, Yongil; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
We present the fabrication (using a hydrothermal process) and the properties of wearable fabrics decorated with ultrathin manganese oxide (MnO2) nanorods for supercapacitor applications. The superior mechanical durability of the supercapacitor was confirmed by cyclic voltammetry (CV) curves, which showed little change during 1000 bending cycles. The pseudocapacitive properties of the ultrathin MnO2 nanorods were confirmed by recording the CV curves at various scan rates. The galvanostatic charge-discharge curves at various specific currents confirmed the pseudocapacitance of MnO2. The ultrathin MnO2 nanorods exhibited a superior capacitance of 508 F.g(-1) and an energy density of 35.3 Wh.kg(-1). The MnO2 electrode with optimal properties demonstrated stable long-term cycling performance with 90% retention after 10,000 galvanostatic cycles.
Keywords: Cotton fabric; Manganese oxide; Ultrafine nanostructures; Wearable supercapacitors

Flexible metallized carbon nanofibers decorated with two-dimensional NiGa2S4 nanosheets as supercapacitor electrodes - Kim, Yongil; Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Lee, Hae-Seok; Yoon, Sam S. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Herein, high-power flexible supercapacitor electrodes were fabricated by decorating Ni-electroplated carbon nanofibers (Ni@CNF) with two-dimensional NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets. The electrical conductivity of carbon nanofibers was enhanced by the addition of nickel, and the energy storage capability was enhanced by decoration with NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The impact of metal (Ni/Ga) ratio on the overall electrochemical performance of the supercapacitor was studied by varying the Ga concentration. The NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> nanosheets promoted diffusion of the electrolyte into the electrode, thereby improving the electrochemical activity. The nanosheets also intensified the charge transfer rate within the composite electrode, which contributed to the overall improvement in the electrochemical performance. The optimal Ga concentration was the concentration at which the specific capacitance was the highest at 488 F·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> with a potential window of 1.1 V and current rate of 0.5 A·g<span style="font-size: 13.5px; line-height: 0; position: relative; top: -0.5em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">−1<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The long-term stability test revealed that the capacitance retention of the electrode with this optimal Ni/Ga ratio was 109% after 20,000 cycles. This flexible supercapacitor electrode was subjected to 2000 bending cycles, and the corresponding cyclic voltammetry performance was assessed. In combination, the outstanding electrochemical performance and durable mechanical properties render the NiGa<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">4<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/Ni@CNF electrode highly suitable for flexible energy storage applications.

Electrospun zinc-manganese bimetallic oxide carbon nanofibers as freestanding supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yongil; Kim, Taegun; El-Newehy, Mohamed; Aldalbahi, Ali; Yoon, Sam S. (International Journal of Energy Research, 2022)
Flexible, lightweight, and freestanding zinc-manganese oxide carbon nanofibers are promising materials for the fabrication of portable electronic devices. Composite nanofibers were synthesized using terephthalic acid and sodium dodecyl sulfate. Terephthalic acid improves the flexibility of the composite fibers and facilitates the diffusion of electrolytic ions. Meanwhile, sodium dodecyl sulfate aids to elevate the metal (zinc) oxide particles to the surface of the nanofibers during annealing. The texturing of the carbon nanofiber surface with ZnO enhances the electrochemical activity of the composite fibers. Parametric studies were conducted by varying the weight ratio of zinc and manganese acetates from zero to unity. The optimal case with a ratio of 0.75 produces specific capacitances of 1080 and 817 F center dot g(-1) at current densities of 1 and 10 A center dot g(-1), respectively, with a wide potential window of 1.6 V, indicating outstanding energy storage capabilities. The capacitance retention was 92% after 10 000 galvanostatic charge-discharge cycles. The bending angle test confirmed the mechanical durability of the freestanding carbon nanofiber electrodes, and the corresponding change in the cyclic voltammetry curve was negligible.
Keywords: electrospinning; freestanding electrode; high-energy-density; supercapacitor; ZnMn2O4

Formation of zircon-type DyCrO4 and its magnetic properties - Ughade, Supriya; Joshi, Bhavana; Poddar, Pankaj (Ceramics International, 2022)
The formation mechanism of hydrolytic sol-gel synthesized DyCrO4 with a complexing agent in acidic and basic mediums is thoroughly studied. The role of complexing agents and pH on phase formation temperature is also intensively investigated. The formation temperature for DyCrO4 is similar to 500 degrees C in the absence and presence of complexing agents such as oxalic acid and ethylenediaminetetraacetic acid (EDTA) at pH 10. When critic acid is used, the DyCrO4 forms with Cr2O3 impurity. The crystallite size in the presence of a complexing agent in the basic medium is similar to 55 nm which is small as compared to only ammonia solution. The various reaction modes lead to tetragonal zircon-type DyCrO4 at similar to 500 degrees C, transforming into orthorhombic perovskite DyCrO3 at 800 degrees C. The magnetization curve shows the ferromagnetic behavior of DyCrO4 below transition temperature T-c similar to 21 K. This low T-c makes nanocrystalline DyCrO4 a potential material for cryogenic applications.
Keywords: Complexing agent; DyCrO4; Formation mechanism; Hydrolytic sol-gel method; pH

Progress and potential of electrospinning-derived substrate-free and binder-free lithium-ion battery electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Yarin, Alexander L.; Swihart, Mark T.; Yoon, Sam S. (Chemical Engineering Journal, 2022)
Carbon nanofibers derived from electrospun precursors show great promise for electronic applications owing to their flexibility, conductivity, high surface area, and open structure. The integration of metal oxides and sulfides in carbon nanofibers, rather than using them with other binders, eliminates many problems caused by poor adhesion, nanomaterial agglomeration, excess mass contributed by inactive binders, and low conductivity of embedded active materials. The engineering of electrospun fibers with novel morphologies, such as core-shell, hollow, or porous structures, and the use of decorated carbon nanofibers (e.g., by electrodeposition or co precipitation) are discussed in this review. Representative schematic illustrations of the lithium-storage mechanism for these binder-free electrodes are presented. We describe how the electrospinning technique can offer a cost-effective strategy for fabrication of lightweight lithium-ion batteries with high capacity and excellent bendability. This review presents the fascinating morphologies of these specially designed carbon nanofiber electrodes, which enhance the electrochemical performance of metal oxides and sulfides, illustrating their enormous potential for use in wearable electronic devices and hybrid electric vehicles.
Keywords: Carbon nanofibers; Co-axial; composites; core-shell; electrospinning; Flexible

Review of recent progress in electrospinning-derived freestanding and binder-free electrodes for supercapacitors - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Yarin, Alexander L.; Swihart, Mark T.; Yoon, Sam S. (Coordination Chemistry Reviews, 2022)
The versatile electrospinning technique is scalable and suitable to fabricate highly conducting freestanding carbon nanofiber composite electrodes for energy storage devices. Freestanding/flexible electrodes hold enormous potential for use in wearable electronic devices. Carbon-yielding polymers and the optimal use of sacrificial polymers, metal oxides, and sulfides retain the flexibility and enhance the surface area and pseudocapacitance of electrodes. Both as-prepared electrospun fibers and carbonized nanofibers are compatible with surface decoration via various chemical and electrochemical routes. Metal oxides/sulfides with various morphologies, such as nanocones and nanosheets, can be grown on the carbon nanofibers or on the as-prepared electrospun fibers using chemical synthesis methods such as electro-deposition, hydrothermal processes, and chemical impregnation to enhance the pseudocapacitance of the electrodes. Similarly, the deposition of metal organic frameworks on as-prepared electrospun fibers embellishes these fibers with nanostructures of specific morphologies such as dodecahedral and spindle-shaped structures. Under optimal conditions, these morphologies do not hamper the flexibility of the fibers, and binders are not required to retain them or maintain the electrode integrity. The engineering of electrodes with various morphologies and process parameters is presented systematically. Electrospinning-derived electrodes that have demonstrated significant electrochemical performance are highlighted and critically analyzed, and the energy storage mechanisms of these supercapacitors are described in detail. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Carbon nanofibers; Co-axial; composites; core-shell; electrospinning; Flexible; Porous; supercapacitor

Wearable fabric supercapacitors based on CNTs and polyhedral ZnO with a wide potential window - Samuel, Edmund; Joshi, Bhavana; Park, Chanwoo; Aldalbahi, Ali; El-Newehy, Mohamed; Lee, Hae-Seok; Yoon, Sam S. (International Journal of Energy Research, 2022)
Wearable electronic devices such as health monitors, sensors, and e-skin can be powered by lightweight, high-power supercapacitors. Using a binder-free and low-temperature hydrothermal method, polyhedral ZnO nanoparticles were grown on carbon nanotube (CNT)-decorated cotton fabric, which is friendly to human skin and highly wearable, inexpensive, and thus commercially viable. The concentration of the starting material, zinc acetate, was varied to optimize the electrochemical performance. The evenly spaced polyhedral ZnO facilitated efficient permeation of the electrolyte into the active material. The fabric filaments were decorated with CNTs to enhance electron transfer and the overall electrochemical processes. The symmetric cell comprised of cotton fabric decorated with ZnO polyhedron/CNT showed no discernible change in the cyclic voltammetry curves even after 500 bending cycles, demonstrating the mechanical durability of the electrode. The potential window of 1.6 V using a Na2SO4/K2SO4 aqueous dual-ion electrolyte improved the long-term electrochemical stability and increased the energy storage capacity. The capacitance retention was 94% after 5000 cycles at a current density of 1 A center dot g(-1), indicating long-term electrochemical stability. A specific capacitance of 375 F center dot g(-1) at a current density of 5 A center dot g(-1) and energy density of 33.3 Wh center dot kg(-1) at a power density of 2000 W center dot kg(-1) were recorded for the optimized electrode. Highlights Polyhedral ZnO was grown on cotton fabric using a hydrothermal process. The electrochemical performance was optimized by varying the zinc acetate concentration. The highest specific capacitance was 375 F center dot g(-1) at a current density of 5 A center dot g(-1). Under optimal conditions, the capacitance retention was 94% at N = 5000 cycles. The energy density of the electrode was as high as 33.3 Wh center dot kg(-1).
Keywords: carbon nanotube; Cotton fabric; hydrothermal process; wearable supercapacitor; ZnO polyhedron

Ferroelectric polarization and iron substitution synergistically boost electrocatalytic oxygen evolution reaction in bismuth oxychloride nanosheets - Singh, Dinesh; Joshi, Bhavana; Poddar, Pankaj (Langmuir, 2023)
Ferroelectric materials have gained significant interestin variouskinds of water splitting, but the study of ferroelectric materialsfor electrocatalytic water splitting is in its infancy. Ferroelectricmaterials have spontaneous polarization below their Curie temperaturedue to dipolar alignment, which results in surface charges. In 2Dferroelectric materials, spontaneous polarization depends on thickness.Herein, we report that thickness-dependent ferroelectric polarizationin 2D nanosheets can also accelerate the oxygen evolution reaction(OER) along with the tailored active surface area of exposed crystallinefacets, which improves the electrocatalytic activity relatively. Iron-substitutedBiOCl nanosheets of varying thickness are fabricated by varying thepH using a facile coprecipitation method. The substituted iron enhancespolarization and electrochemical active sites on the surface. Thefindings in this study show that the exposed (001) facet and higherthickness of the nanosheets have high ferroelectric polarization and,in turn, superior electrocatalytic activity and remarkable stability,requiring low overpotentials (348 mV and 270 mV at 100 mA/cm(2) and 10 mA/cm(2)) in alkaline (1.0 M KOH) electrolyte. Asthe thickness of the nanosheets is decreased from 140 to 34 nm, theelectrocatalytic performance of iron-substituted BiOCl nanosheetsstarts to reduce due to the lower Coulomb-Coulomb interactionand the increasing depolarization.

Poly(N-vinylpyrrolidone)-assisted crystal growth of zeolitic imidazolate framework (ZIF-67) and electrochemical properties of its derivatives for flexible supercapacitors - Jain, Manisha; Joshi, Bhavana; Poddar, Pankaj (Crystal Growth and Design, 2024)
A simple and explicit wet chemical method enables the room-temperature crystallization of the zeolitic imidazolate framework (ZIF-67) using cotton-cloth (CC) as a substrate; where time-dependent Avrami's kinetic studies demonstrated sluggish nucleation and fast crystal growth resulting in unprecedented morphologies-truncated cubes [synthesized without poly(N-vinylpyrrolidone); PVP], and rhombic dodecahedra (with PVP) with average sizes ranging from 500 nm to 1.41 mu m; wherein amphiphilic PVP plays a crucial function of structure directing agent by modulation of complex formation and deprotonation equilibria. To study the potential of pristine ZIF-67 (ZP0) and PVP-functionalized ZIF-67 (ZP50, ZP100, and ZP200) grown on the CC substrate for application as a flexible electrode in supercapacitors, ZP0, ZP50, ZP100, and ZP200 were annealed to form CZP0, CZP50, and CZP100, respectively. Areal capacitances of 181 and 214 mFcm(-2) were achieved at a current density of 1 mAcm(-2) and a potential window of 1.6 V for CZP0 and CZP100, respectively, and compared to the derivatives without PVP; CZP100 exhibited a superior energy density of 76.3 mu Whcm(-2) and a capacitance retention of 84.3% after 5000 cycles at a current density of 0.5 mAcm(-2).